Characterizing fluvial impact on the biochemical composition of particulate organic matter in the Laptev Sea and Western East Siberian Sea during the late summer of 2018 - Naeun Jo; Kwanwoo Kim; Hyo Keun Jang; Sanghoon Park; Jaesoon Kim; Terry E. Whitledge; Dean A. Stockwell; Sang Heon Lee (Science of The Total Environment, 2024)

Size-differential photosynthetic traits of phytoplankton in the Chukchi Sea - Sang H. Lee; Mi Sun Yun; Hyo Keun Jang; Jae Joong Kang; Kwanwoo Kim; Dabin Lee; Naeun Jo; Sang Hoon Park; Jang Han Lee; So Hyun Ahn; Dean A. Stockwell; Terry E. Whitledge (Continental Shelf Research, 2023)

The biochemical composition of phytoplankton in the Laptev and East Siberian seas during the summer of 2013 - So Hyun Ahn; Terry E. Whitledge; Dean A. Stockwell; Jang Han Lee; Ho won Lee; Sang Heon Lee (Polar Biology, 2019)

The Relationship Between Patterns of Benthic Fauna and Zooplankton in the Chukchi Sea and Physical Forcing - Maria Pisareva; Robert Pickart; Katrin Iken; Elizaveta Ershova; Jacqueline Grebmeier; Lee Cooper; Bodil Bluhm; Carolina Nobre; Russell Hopcroft; Haoguo Hu; Jia Wang; Carin Ashjian; et al. (Oceanography, 2015)

Recent phytoplankton productivity of the northern Bering Sea during early summer in 2007 - Sang H. Lee; Hyoung Min Joo; Mi Sun Yun; Terry E. Whitledge (Polar Biology, 2012)

Holes in Progressively Thinning Arctic Sea Ice Lead to New Ice Algae Habitat - Sang Heon Lee; C. Peter McRoy; Hyoung Min Joo; Rolf Gradinger; Huehua Cui; Mi Sun Yun; Kyung Ho Chung; Sung-Ho Kang; Chang-Keun Kang; Eun Jung Choy; SeungHyun Son; Eddy Carmack; et al. (Oceanography, 2011)

Comparison of bottom sea-ice algal characteristics from coastal and offshore regions in the Arctic Ocean - Sang H. Lee; Meibing Jin; Terry E. Whitledge (Polar Biology, 2010)

Uptake rates of dissolved inorganic carbon and nitrogen by under-ice phytoplankton in the Canada Basin in summer 2005 - Sang H. Lee; Dean Stockwell; Terry E. Whitledge (Polar Biology, 2010)

Primary and new production in the deep Canada Basin during summer 2002 - Sang H. Lee; Terry E. Whitledge (Polar Biology, 2005)

The Northeast Pacific GLOBEC Program: Coastal Gulf of Alaska - Thomas Weingartner; Kenneth Coyle; Bruce Finney; Russell Hopcroft; Terry Whitledge; Richard Brodeur; Michael Dagg; Edward Farley; Dale Haidvogel; Lew Haldorson; Al Hermann; Sarah Hinckley; et al. (Oceanography, 2002)

Anomalous conditions in the south‐eastern Bering Sea, 1997: nutrients, phytoplankton and zooplankton - Dean A. Stockwell; Terry E. Whitledge; Stephan I. Zeeman; Kenneth O. Coyle; Jeffrey M. Napp; Richard D. Brodeur; Alexei I. Pinchuk; George L. Hunt (Fisheries Oceanography, 2001)
Anomalies in the regional weather over the south‐eastern Bering Sea during spring and summer of 1997 resulted in significant differences in nutrient availability, phytoplankton species composition, and zooplankton abundance over the continental shelf as compared with measurements in the 1980s. Calm winds and the reduction of cloud cover in spring and summer produced a very shallow mixed layer in which nitrate and silicate were depleted after an April diatom bloom. High submarine light levels allowed subsequent phytoplankton growth below the pycnocline and eventual depletion of nitrate from the water column to depths of 70 m or more. Thus, total new production during 1997 may have exceeded that of previous years when nitrate was not depleted below the pycnocline. A bloom of the coccolithophorid, Emiliania huxleyi , was observed in early July in the warm, nutrient‐depleted waters over the middle and inner shelf. Emiliania huxleyi concentrations reached 4.5 × 10 6 cells L –1 by September, and the bloom persisted through the autumn. There was evidence for increased abundance of some species of copepods in 1997 as compared with data from the middle domain in June 1981. The abundance of adult and juvenile euphausiids in 1997 was statistically similar to values measured in 1980 and 1981. However, near‐surface swarms were rarely observed on the inner shelf in August–September 1997. Lack of euphausiid availability in the upper water column may partially explain the August–September mass mortality of planktivorous short‐tailed shearwaters ( Puffinus tenuirostris ) observed on the inner shelf.

Disruption of grazer populations as a contributing factor to the initiation of the Texas brown tide algal bloom - Edward J. Buskey; Paul A. Montagna; Anthony F. Amos; Terry E. Whitledge (Limnology and Oceanography, 1997)
Disruption of grazer populations, or mismatches between phytoplankton blooms and population dynamics of their planktonic and benthic grazers, may play an important role in the initiation of some harmful algal blooms. The Laguna Madre of Texas has experienced a persistent, nearly monospecific phytoplankton bloom since January 1990 commonly referred to as the “brown tide.” Whole‐water samples collected in the area where the bloom began reveal the pattern of bloom initiation and dispersion during the first few months of the bloom. Enumeration of microzooplankton from these same samples also reveals that protozoan grazer populations were depressed and nearly eliminated before the bloom began. Benthic biomass and species diversity also declined before the onset of the bloom. The disruption of planktonic and benthic grazers may have been due to extreme hypersaline conditions caused by an extended period of drought (salinities > 60‰). A massive fish kill caused by an abnormal period of below freezing temperatures released a pulse of nutrients into an already disturbed environment allowing this nuisance bloom to become established. Planktonic and benthic grazers have been unable to contribute to the demise of this bloom, which has persisted for >7 yr without interruption.